2022
DOI: 10.1186/s13071-021-05144-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition in Hyalomma anatolicum collected from livestock in the United Arab Emirates using next-generation sequencing

Abstract: Background Hyalomma anatolicum is a widely distributed tick species that acts as a vector transmitting tick-borne pathogens (TBPs) in livestock. Such pathogens affect the health of livestock and consequently reduce their productivity. Knowledge about the microbial communities (pathogens and endosymbionts) of ticks in the United Arab Emirates (UAE) is scarce. Therefore, the aim of the present study was to quantify microbial diversity in H. anatolicum using next-generation sequencing (NGS) techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Staphylococcus, Bacillus, Francisella , and Corynebacterium were the most common genera in all months, and the results were a little different from the results of our previous finding where Acinetobacter and Corynebacterium were the most common genera in 2010 and Francisella in 2019 ( 22 ). Focusing on Francisella , the sequences have already been detected in all studies on H. dromedarii and a study on Hyalomma anatolicum characterizing microbial composition in the MENA region ( 22 , 33 35 , 49 ). In the present study, Francisella was detected with high relative abundance in September followed by April and October.…”
Section: Discussionmentioning
confidence: 97%
“…Staphylococcus, Bacillus, Francisella , and Corynebacterium were the most common genera in all months, and the results were a little different from the results of our previous finding where Acinetobacter and Corynebacterium were the most common genera in 2010 and Francisella in 2019 ( 22 ). Focusing on Francisella , the sequences have already been detected in all studies on H. dromedarii and a study on Hyalomma anatolicum characterizing microbial composition in the MENA region ( 22 , 33 35 , 49 ). In the present study, Francisella was detected with high relative abundance in September followed by April and October.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, it had previously been reported as persistent in a mass rearing colony and a wild population of Anagyrus vladimiri but with low abundance (<1%) (Izraeli et al, 2021 ). However, higher abundance of Carnimonas (32%) was recently identified in Hyalomma anatolicum ticks; meanwhile, the authors suggested a negative association between Klebsiella and Carnimonas (Perveen et al, 2022 ). So far, little is known about the role of Carnimonas .…”
Section: Discussionmentioning
confidence: 98%